Keterampilan Menulis Puisi Bugis Menggunakan Media Audiovisual Siswa Kelas IX MTs. Puteri Pusat Sengkang Kabupaten Wajo - Novia Wahyuni, Nopi; Syamsudduha; Nurhusna (Journal of Applied Linguistics and Literature, 2024)
This research aims to describe the skills of writing Bugis poetry using audiovisual media of class IX Mts students. Puteri Sengkang Center, Wajo Regency. The population in this study was all class IX Mts. The number of Sengkang Central Girls in Wajo Regency is 362 people consisting of 14 classes. The sample for this research was 53 people from two different classes, namely IX.1 and IX.7 using purposive sampling. This research uses data collection techniques in the form of written tests. The research results showed that the highest score was in the 80-89 range obtained by 28 samples with a percentage (53%) in the skilled category. Minimum Completeness Criteria for Writing Bugis Poetry at MTs Schools. Puteri Pusat Sengkang was declared Complete because 47 students got a score of 74-100 with a percentage of 89% and 6 people got a score of 0-74 with a percentage of 11%.